2011
DOI: 10.1007/s11069-011-9719-6
|View full text |Cite
|
Sign up to set email alerts
|

Scaling property of regional floods in New South Wales Australia

Abstract: Regional flood frequency analysis (RFFA) is often used in hydrology to estimate flood quantiles when there is a limitation of at-site recorded flood data. One of the commonly used RFFA methods is the index flood method, which is based on the assumptions that a region satisfies criterion of simple scaling and it can be treated homogeneous. Another RFFA method is quantile regression technique where prediction equations are developed for flood quantiles of interest as function of catchment characteristics. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 29 publications
(43 reference statements)
2
23
0
Order By: Relevance
“…Previous investigators have sought to identify well‐behaved, homogenous regions suitable for the application of techniques like the index‐flood method [ Skaugen and Vaeringstad , ]. Because of the practical importance of the problem, most research on spatial scaling has focused on flood flows [ Gupta and Waymire , ; Smith , ; Gupta et al ., ; Dawdy and Gupta , ; Gupta and Dawdy , ; Pandey , ; Eaton et al ., ; Yue and Gan , ; Ishak et al ., ]. Additionally, some studies have examined the scaling behavior of mean annual flows: Vogel and Sankarasubramanian [] found that U.S. mean annual flows exhibited simple scaling while Yue and Gan [] and Buttle and Eimers [] reached similar conclusions with respect to flows in Canada.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous investigators have sought to identify well‐behaved, homogenous regions suitable for the application of techniques like the index‐flood method [ Skaugen and Vaeringstad , ]. Because of the practical importance of the problem, most research on spatial scaling has focused on flood flows [ Gupta and Waymire , ; Smith , ; Gupta et al ., ; Dawdy and Gupta , ; Gupta and Dawdy , ; Pandey , ; Eaton et al ., ; Yue and Gan , ; Ishak et al ., ]. Additionally, some studies have examined the scaling behavior of mean annual flows: Vogel and Sankarasubramanian [] found that U.S. mean annual flows exhibited simple scaling while Yue and Gan [] and Buttle and Eimers [] reached similar conclusions with respect to flows in Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Typical of the wider literature, the studies reviewed for this work almost exclusively considered drainage area alone when examining scaling behavior [ Yue and Gan , ; Yue and Wang , , among others], though some studies consider, at most, one or two other explanatory variables, including precipitation [ Modarres , ] and rainfall intensities and stream density [ Ishak et al ., ]. Ishak et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most important objectives in regional Flood Frequency Analysis (FFA) is to design flood estimates for regions for which there are no observational data. Flood estimates have been used to design hydraulic structures, such as dams, cheddars, brigs, channels, and other structures that are used in flood management (Aziz, Rahman, Fang, & Shrestha, ; Cunnane, ; Ishak, Haddad, Zaman, & Rahman, ; Merz & Blöschl, ; Ouarda, Girard, Cavadias, & Bobee, ; Taylor, Haddad, Zaman, & Rahman, ). The risk of damage from flooding can be greatly reduced if the construction of various structures and the development of towns and villages are based on flood forecasting and information.…”
Section: Introductionmentioning
confidence: 99%
“…2) with a maximum of 2.5 m in some areas. Several methods have been proposed for creating flood estimation models for areas lacking gauging stations by using empirical, regression, curve number method, for determining the rainfall-runoff relationships [Ishak et al, 2011;Liu et al, 2011;Subyani, 2011;Sen 2008a]. In the present work we aim to use the SCS (Soil Conservation System) Curve Number method to create a flood hazard zone based on runoff values from rainfall data for the flooding event of November 23-24th 2006.…”
Section: Introductionmentioning
confidence: 99%